ผลการใช้กระบวนการเรียนการสอนโดยใช้การพัฒนาบทเรียนร่วมกันและการเป็นพี่เลี้ยงเพื่อเสริมสร้างความสามารถในการประยุกต์ทฤษฎีสู่การปฏิบัติการสอนคณิตศาสตร์สำหรับเด็กปฐมวัย ของนิสิตชั้นปีที่ 3 สาขาวิชาการศึกษาปฐมวัย - จารุชัยนิวัฒน์, ปนัฐษรณ์ (Journal of Education Studies, Chulalongkorn University, 2019)
This research aimed to study the effects of using instructional process based on lesson study and mentoring to enhance abilities in applying theories into mathematics teaching practice for young children of the third year early childhood education students. The target was 17 third year early childhood education students who enrolled in Development of Mathematics, Science, and Technology Learning for Young Children course in the second semester of the academic year 2016. This study can be divided into 2 phrases, 16 week-action research which utilized the pedagogical knowledge in mathematics for young children test and the teaching mathematics to young children evaluation form in data collection. The data were collected 4 times and analyzed using means, standard deviation and repeated measure with interaction. The ﬁndings were as follows: 1) after the instructional process, the total average post-test scores of the students’ pedagogical knowledge in mathematics for young children were higher than those of the pre-test. 2) After each phrase of the implementation of the Type 1 and the Type 2 instructional process, the total average scores of the abilities in teaching mathematics to young children of the students, which were measured 4 times, were continuously increased.